Towards sustainable campuses: a case study of an international school in Singapore - Mohamed Nabil Bin Mohamed Yazeed (Nanyang Technological University, 2024)
Environmental sustainability in educational institutions has steadily gained prominence with campuses increasingly recognizing the need to reduce their resource consumption and carbon footprint in line with the UN Sustainable Development Goals. While educational institutions have sought to integrate sustainability across various areas, much of the focus has been on sustainable campus operations as these operations usually account for the largest share of institutional expenditures and results in the greatest environmental impact. This study examines sustainable campus operations at the East Campus of UWCSEA, a K-12 international school system in Singapore, through an integrated approach combining environmental data analysis with a review of sustainability initiatives. By analysing data on energy consumption, water usage, and cooling loads, this study aims to identify trends in resource use in order to inform future efforts for further optimisation. The campus’s sustainability initiatives, spanning buildings, energy, food systems, procurement and transportation, will also be analysed in the context of best practices in buildings and campuses worldwide. Findings reveal opportunities for further improvement through renewable energy integration, occupancy-responsive systems, and enhanced sustainability education. Nevertheless, challenges such a need to integrate behavioral insights may guide future research in exploring the role of stakeholder engagement in building a sustainability-oriented culture for campus operations.